PERBANDINGAN DUA KITAB SYARAH ṢAḤĪḤ AL-BUKHĀRĪ: FATḤ AL-BĀRĪ DAN ‘UMDAT AL-QĀRĪ - Rustina N Rustina N (Pascasarjana IAIN Ambon, 2022)
This paper aims to describe the method adopted by Ibn Hajar al-Asqalani and Badr al-Din al-Aini in explaining the meaning and content of the traditions of the Prophet. in his two syarah books, respectively, Fath al-Bari Syarah Sahih al-Bukhari and the book Umdat al-Qari syarah Sahih al-Bukhari. Furthermore, a comparison is made to find the similarities and differences of the two books so that the advantages and privileges of each can be known. In this study, a qualitative descriptive method was used. Is a type of library research whose data comes from literature in the form of books Data analysis was carried out using content analysis techniques. The results of this study; The similarities are found in the two books using the tahliliy and muqaran methods, which explain the meaning of the content of hadith from various aspects the strongest; put forward the asbab al-wurud hadith and relate it to the appropriate verse. These two books also state differences in the pronunciation of hadith in other narrations, and compare the opinions of the scholars in each discussion. The difference is, Fath al-Bari covers a lot of scientific discussion, including contextual analysis by looking at the asbab wurud hadith or doing grammatical analysis, and the socio-cultural conditions of society when a hadith appears. The approach used in Syar Fatḥ al-Bārī uses a linguistic, multi-disciplinary, and historical approach. Meanwhile, Umdat al-Qari is more dominated by linguistic aspects, both grammatical aspects and i'rab, sharfi, bayan and ma'aniy aspects, so this book can be said to use a linguistic approach or style (linguistics). In terms of writing techniques in Fath al-Bari found repeated explanations (mukarrar) in several places without any additional explanation. Al-Aini to be more consistent in the application of systematics. In various places to clarify his syarah, al-Aini applies the question and answer method so that it is called a characteristic of this book.Tulisan ini bertujuan mendeskripsikan metode yang ditempuh oleh Ibnu Hajar al-Asqalani dan Badr al-Din al-Aini dalam menjelaskan makna hadis-hadis Nabi saw. dalam dua kitab syarahnya masing-masing, Fath al-Bari Syarah Shahih al-Bukhari dan kitab Umdat al-Qari Syarah Shahih al-Bukhari. Selanjutnya dilakukan perbandingan untuk menemukan persamaan dan perbedaan dua kitab tersebut sehingga dapat diketahui keunggulan dan keistimewaan masing-masing. Dalam kajian ini digunakan metode deskriptif kualitatif. Merupakan jenis penelitian pustaka yang data-datanya bersumber dari literatur berupa buku atau kitab. Analisis data dilakukan dengan teknik analisis isi. Hasil penelitian ini; Persamaannya ditemukan kedua kitab menggunakan metode tahliliy dan muqaran, yakni menjelaskan makna kandungan hadis dari berbagai aspek mengemukakan asbab al-wurud hadis serta mengaitkan dengan ayat yang sesuai. Kedua kitab ini juga mengemukakan perbedaan lafaz hadis pada riwayat lain, dan membandingkan pendapat para ulam. Perbedaan yaitu, Fath al-Bari banyak mencakup pembahasan ilmiah, meliputi analisis kontekstual dengan melihat asbab wurud atau melalukan analisis gramatika, dan kondisi sosial budaya masyarakat ketika munculnya suatu hadis. Pendekatan yang digunakan Fatḥ al-Bār model pendekatan linguistik, multi disipliner, dan pendekatan historis. Sedangkan Umdat al-Qari lebih didominasi pada pensyarahan aspek kebahasaan, baik aspek gramatika maupun i’rab, sharfi, aspek bayan dan ma’aniy, sehingga disebut bercorak kebahasaan (linguistik). Dari segi teknik penulisan dalam Fath al-Bari ditemukan penjelasan yang berulang (mukarrar) tanpa ada penjelasan tambahan. Al-Aini cenderung lebih konsisten dalam penerapan sistematika Kasus seperti ini tidak ditemukan dalam Umdat al-Qari. Dalam berbagai tempat untuk memperjelas syarahannya al-Aini menerapkan metode tanya jawab sehingga disebut sebagai ciri khas kitab ini.